2011
DOI: 10.1128/aac.00887-10
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Population Pharmacokinetic Modeling of Lopinavir and Ritonavir in Healthy Volunteers and Assessment of Different Dosing Strategies

Abstract: Nonlinear mixed-effects modeling was applied to explore the relationship between lopinavir and ritonavir concentrations over 72 h following drug cessation and also to assess other lopinavir and ritonavir dosing strategies compared to the standard 400-mg-100-mg twice-daily dose. Data from 16 healthy volunteers were included. Possible covariates influencing lopinavir and ritonavir pharmacokinetics were also assessed. Data were modeled first separately and then together by using individually predicted ritonavir p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 13 publications
7
23
2
Order By: Relevance
“…RTV disposition was also best described by our one‐compartmental model with first‐order absorption and elimination, consistent with previous studies . Considering the values of k a reported for RTV when coadministered with LPV or darunavir (DRV) and our results, the RTV k a is not likely to be affected by the coadministered PI.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…RTV disposition was also best described by our one‐compartmental model with first‐order absorption and elimination, consistent with previous studies . Considering the values of k a reported for RTV when coadministered with LPV or darunavir (DRV) and our results, the RTV k a is not likely to be affected by the coadministered PI.…”
Section: Discussionsupporting
confidence: 90%
“…RTV disposition was also best described by our one‐compartmental model with first‐order absorption and elimination, consistent with previous studies . Considering the values of k a reported for RTV when coadministered with LPV or darunavir (DRV) and our results, the RTV k a is not likely to be affected by the coadministered PI. However, in the RTV‐boosted ATV regimens in the present study, CL/F RTV was almost half of the value reported for this parameter in RTV‐boosted LPV or DRV regimens, and therefore, plasma concentrations were higher .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have reported single compartmental elimination kinetics for ritonavir [8, 20–22]. However, possibly because of the rich sampling schedule used in our study, a two compartment model was more appropriate to describe the kinetics in our data.…”
Section: Discussionmentioning
confidence: 98%
“…higher doses and/or other target populations. However, extrapolation beyond the range of the data should be applied with caution [8, 9].…”
Section: Introductionmentioning
confidence: 99%